Taxation of income and wealth in a model of endogenous growth - Hans Peter Grüner; Burkhard Heer (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
This paper explores the effects of inheritance taxation and income taxation on the growth rate in an endogenous growth model with altruistic parents. Human capital is accumulated according to the Standard Lucas specification. The government raises taxes in order to finance a non-productive public good. The public good must be provided in a fixed proportion to output. Pure wealth taxation is proven to deliver a higher steady-state growth rate than any feasible mix of income and wealth taxation.
Keywords: E62; O11; 330; Optimal Taxation; Endogenous Growth; Inheritance Taxation